2020
DOI: 10.1096/fj.202001180r
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide, oxygen, and calcium regulation in developing human airway smooth muscle

Abstract: Preterm infants can develop airway hyperreactivity and impaired bronchodilation following supplemental O2 (hyperoxia) in early life, making it important to understand mechanisms of hyperoxia effects. Endogenous hydrogen sulfide (H2S) has anti‐inflammatory and vasodilatory effects with oxidative stress. There is little understanding of H2S signaling in developing airways. We hypothesized that the endogenous H2S system is detrimentally influenced by O2 and conversely H2S signaling pathways can be leveraged to at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 94 publications
(240 reference statements)
0
2
0
Order By: Relevance
“…Corticosteroid use in asthma in controlling inflammation is limited by the side effects and by insensitivity in some people ( Cazzola and Hanania, 2006 ; Bousquet et al, 2007 ; Kuna et al, 2007 ; Heffler et al, 2018 ). It is becoming increasingly clear that several airway diseases are associated with a state of H 2 S deficiency ( Chen et al, 2009a ; Chen et al, 2009b ; Bartman et al, 2020 ; Hughes et al, 2009 ). We have previously demonstrated the ability of H 2 S donors such as NaHS to modulate bronchial tone and reverse AHR ( Roviezzo et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroid use in asthma in controlling inflammation is limited by the side effects and by insensitivity in some people ( Cazzola and Hanania, 2006 ; Bousquet et al, 2007 ; Kuna et al, 2007 ; Heffler et al, 2018 ). It is becoming increasingly clear that several airway diseases are associated with a state of H 2 S deficiency ( Chen et al, 2009a ; Chen et al, 2009b ; Bartman et al, 2020 ; Hughes et al, 2009 ). We have previously demonstrated the ability of H 2 S donors such as NaHS to modulate bronchial tone and reverse AHR ( Roviezzo et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies using human fetal airway smooth muscle have shown dose-dependent effects with moderate oxygen increasing proliferation and higher levels (>60%) driving apoptosis ( 102 ). Furthermore, studies on human fetal airway smooth muscle have shown moderate hyperoxia increases airway hyperreactivity via intracellular calcium response to bronchoconstrictor agonists ( 102 , 142 , 143 ). In vivo studies using moderate hyperoxia in a neonatal mouse model have demonstrated structural and functional changes similar to those seen in asthma and reactive airway disease: increased airway hyperreactivity in response to methacholine challenge as well as increased ASM thickness and collagen deposition in the airway ( 100 , 132 ).…”
Section: Oxygen and Pediatric Airway Diseasementioning
confidence: 99%